2021
DOI: 10.3390/jcm10184186
|View full text |Cite
|
Sign up to set email alerts
|

Medically Serious Suicide Attempts in Personality Disorders

Abstract: Medically serious suicide attempts (MSSA) represent a subgroup of clinically heterogeneous suicidal behaviors very close to suicides. Personality disorders (PD) are highly prevalent among them, together with affective and substance use disorders. However, few studies have specifically analyzed the role of PD in MSSA. These suicide attempts (SA) are usually followed by longer hospitalization periods and may result in severe physical and psychological consequences. The aim of this study is to compare the profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The significance of diagnoses related to substance use disorders and personality disorders in patients with suicide attempts aligns with findings in other studies [16] [17] [18] [19] [20] evaluating suicide attempts at a university hospital.…”
Section: Discussionsupporting
confidence: 84%
“…The significance of diagnoses related to substance use disorders and personality disorders in patients with suicide attempts aligns with findings in other studies [16] [17] [18] [19] [20] evaluating suicide attempts at a university hospital.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have reported the relationship between suicide attempts and personality disorders. [65][66][67] In a meta-analysis study, Pompili et al 68 showed that suicide was the leading cause of death among patients with borderline personality disorder. From 1980 to 2005, on average, 100,000 suicides leading to death worldwide were caused by people with borderline personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that 14.85% of suicide attempters had borderline personality disorder. Several studies have reported the relationship between suicide attempts and personality disorders 65–67 …”
Section: Discussionmentioning
confidence: 99%
“…While deaths by suicide are more frequent among men compared to women, these are more likely to have suicide attempts than men. Signi cantly, they have a similar distribution when it comes to MSSA (14). It is estimated that up to two-thirds of those who complete suicide are not in contact with the mental health services at the time of death (15).…”
Section: Gender Perspectivementioning
confidence: 99%
“…Suicidal ideation and behaviours are known to be in uenced by gender and sex factors (14)(15)(16)(17). While deaths by suicide are more frequent among men compared to women, these are more likely to have suicide attempts than men.…”
Section: Gender Perspectivementioning
confidence: 99%